Somatotopy of cervical dystonia in motor-cerebellar networks: Evidence from resting state fMRI. (January 2022) - Zito, Giuseppe A.; Tarrano, Clément; Jegatheesan, Prasanthi; Ekmen, Asya; Béranger, Benoît; Rebsamen, Michael; Hubsch, Cécile; Sangla, Sophie; Bonnet, Cécilia; Delorme, Cécile; Méneret, Aurélie; Degos, Bertrand; et al.
Abstract: Introduction: Cervical dystonia is the most frequent form of isolated focal dystonia. It is often associated with a dysfunction in brain networks, mostly affecting the basal ganglia, the cerebellum, and the somatosensory cortex. However, it is unclear if such a dysfunction is somato-specific to the brain areas containing the representation of the affected body part, and may thereby account for the focal expression of cervical dystonia. In this study, we investigated resting state functional connectivity in the areas within the motor cortex and the cerebellum containing affected and non-affected body representations in cervical dystonia patients. Methods: Eighteen patients affected by cervical dystonia and 21 healthy controls had resting state fMRI. The functional connectivity between the motor cortex and the cerebellum, as well as their corresponding measures of gray matter volume and cortical thickness, were compared between groups. We performed seed-based analyses, selecting the different body representation areas in the precentral gyrus as seed regions, and all cerebellar areas as target regions. Results: Compared to controls, patients exhibited increased functional connectivity between the bilateral trunk representation area of the motor cortex and the cerebellar vermis 6 and 7b, respectively. These functional abnormalities did not correlate with structural changes or symptom severity. Conclusions: Our findings indicate that the abnormal function of the motor network is somato-specific to the areas encompassing the neck representation. Functional abnormalities in discrete relevant areas of the motor network could thus contribute to the focal expression of CD. Highlights: Cervical dystonia is associated with dysfunctions in cerebello-somatosensory networks. We used resting state fMRI to study abnormal functional connectivity. We revealed somato-specific abnormalities in the motor cortex and the cerebellum in patients. Somato-specific abnormalities contribute to the focal expression of cervical dystonia.